Pengelolaan sampah botol plastik air mineral di Kota Sorong guna menurunkan tingkat pencemaran lingkungan - Julian Kelly Kambu; Eko Agus Martanto; Marlyn Lekitoo (Cassowary, 2019)
Sorong is one of the most advanced and most populous cities in the province of West Papua, with a population of 2016 reaching 232,833 people and a population growth rate of 3.21 percent per year (BPS, 2016). As the most populous city, of course, the problem of waste becomes a significant threat, especially related to the increasing volume of waste production both from households and businesses and also the tendency to dispose of waste improperly that results in environmental pollution. The purpose of this study was to determine the extent of environmental pollution due to plastic waste in the City of Sorong, then look further at the management of mineral water plastic bottles, and determine what factors influence the amount of plastic bottle waste in the City of Sorong. The analytical method used in this research is descriptive qualitative analysis. Based on the results of the study it can be seen that the waste management process is carried out by several parties, among others: carried out by the Government using an integrated management system, then by the community with an individual management system, and by the private sector through the Sorong Raya Garbage Bank. Factors that influence the amount of plastic bottle waste include: The level of community / business actors' knowledge about waste, their attitude about waste management, their behavior in managing waste, and the activities of government administrators such as studies on waste, socialization of facilities and regulations, and the adequacy of the APBD budget. and also external participation.